Analysis of the Poetry Morning at the Window Works of Ts Eliot - Meliani, Ai Sinta (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
Poetry is one of the literary works that usually becomes a medium of expression for someone to express feelings, thoughts, visions and whatever that person feels. The unique characteristics possessed by a poem can differentiate it from other literary works. The form of expressing a feeling through poetry is also often done by famous poets, usually by using language that has semantic meaning and includes rhymes and rhythms in it. One of the famous poets who expresses his thoughts into a poem is Tomas Stearn Eliot, or better known as TS Eliot. One of TS Eliot's poems inspired by his thoughts, visions and feelings is his poem entitled Morning at the Window . This study aims to find out what intrinsic elements are contained in the poem Morning at the Window by TS Eliot. Furthermore, the focus of research in this analysis is to find themes, figurative language, and also images in Morning at the Window poetry. The method used by researchers in this study is a descriptive qualitative research method, using data analysis techniques that refer to the theory put forward by Aminuddin. The results of this study indicate that poverty and misery are the right themes for the poem Morning at the Window. Then there are also two figurative language found in this poem, the first is metaphor and the second is personification. The metaphorical figure of speech is found in the first and sixth lines, while the personification figure of speech is only found in the fifth line. Furthermore, two images are also found in this poem, namely visual imagery and kinestic imagery. Visual images are found in the first, sixth, seventh, and eighth lines. Meanwhile, kinestic imagery is only found in the fourth line. Keywords: TS Elliot, Literary work, Poetry, Intrinsic elements, Morning at the window